Humphrey's mixed-up magic trick - Birney, Betty G. (Birney, Betty G. Humphrey's tiny tales, 2016)
"The students of Room 26 are doing reports about the jobs they want to have when they grow up--and Humphrey the classroom pet hamster helps aspiring magician Miranda show the class about her own dream job"--